The Effect of Competence, Digital Technology, and Locus of Control On Fraud Prevention - Chealsea Anasthasya; Rina Yuliastuty Asmara (Information Technology and Science (ITScience), 2025)
This research aims to analyze the influence of competence, digital technology, and locus of control on fraud prevention in public accounting firms in Central Jakarta. Fraud prevention is an important aspect in maintaining the reliability of financial reports and the integrity of the accounting profession. Auditor competence, the use of digital technology, and individual locus of control are assumed to play an important role in supporting the effectiveness of fraud prevention. This study uses a quantitative method with a survey approach through questionnaires distributed to auditors at several public accounting firms in Central Jakarta. The analytical method used in this study is multiple linear regression analysis to test the influence of each independent variable on fraud prevention. The results show that competence and digital technology have a significant positive effect on fraud prevention, while, locus of control has no significant effect on fraud prevention. This means that the higher the level of auditor competence and the more optimal the use of digital technology, the more effective the fraud prevention efforts will be.